The challenges in the implementation of coastal adaptation projects for the rehabilitation of Tacloban City and its implications to planning - Patacsil, Faith Yoriko T. (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
In November of 2013, the Super Typhoon Yolanda (International name Haiyan) hit the Philippines with unprecedented strength. It produced a storm surge that caused massive damage and a high number of casualties in a number of coastal areas. Due to its proximity to the Pacific to the Pacific Ocean, Tacloban City in Leyte Province bore the highest figures for both damages and casualty. As a response, the Local Government, in partnership with UN Habitat, drafted the Tacloban City Recovery and Rehabilitation Plan (TRRP) in March, 2014. This document, together with rehabilitation plans from other affected LGUs were consolidated in the Comprehensive Recovery and Rehabilitation Plans by the National Government. This study aims to identify the challenges in replicating internationally practiced coastal adaptation measures to the Philippines as proposed in the recovery plans for Tacloban City. The Climate Change adaptation approaches in the physical infrastructure and environmental sector are assessed by the two influential factors, there are its suitability and social acceptability, Findings show that the suitability of the five proposed projects varies in terms of their advantages and disadvantages, degree and expected length of effectivity, the physical conditions of the site, and the capacity to be implemented by the responsible agency. Social Acceptability for each project varies in the levels of governance such as the national, local and the barangay communities, and institutional arrangements among the implementing agencies. Perception survey shows that significant variables for the social acceptability of the coastal communities are the barangay of origin, zone, livelihood and lot ownership type, and household size. Recommendations for selecting suitable measures include undergoing a site assessment, evaluation of the capacity to address potential impacts, timing and length of effectivity, availability of resources and technology, and employing models and prioritization methods. For replicating them, it is recommended to assign the institutional responsibilities according to the capacity of the implementing agency and consider using complementary adaptation measures. To raise the social acceptability among the affected communities, a perception survey should be conducted to identify their needs, information gaps and preferred planning participation. This way, implementing agencies would be guided on how to properly address these concerns.